Contribution of Cottage and Small Scale Industries for Boosting Nepalese Economy - Kharel, Khom Raj; Upadhyaya, Yadav Mani (Tribhuvan University Journal, 2021)
This study aims to examine how the cottage and small scale industries (CSIs)boosting the national economy of Nepal. As per various studies, CSIs play a great role for empowering Nepalese economy in terms of employment generation, resources mobilization, capital mobilization as well as import substitution of Nepalese foreign trade. The study has explored the contribution of these industries in the diversified areas. Development and promotion of cottage and small industries enhance significant impact on national economy having drastic effects on job creation and resources utilization in Nepal. Descriptive and analytical research design has been applied to analyse the data by using simple statistical tools. The results show that there have been positive influences on employment generation and capital mobilization in Nepalese economy. The study demands that there should be paid more attention toward the development of CSIs for increasing contribution of these industries boosting national economy.